Enhancing self-efficacy in reading among ESL learners of IIUM Nilai" - Mohd Yusof, norzilah ([s.n], 2012)
Motivation is an important tool in the learning of a second language. It has been proven that motivation is one of the influences on language learning success. Motivation is an integral factor in reading. As reading is a vital component of learning, motivation in reading in English plays an important role in a learners’ personal reading satisfaction as well as in academic performance. Whilst motivation is an integral factor in reading, it has been found that motivation decline when children go to school.